Pituitary hyperplasia secondary to primary hipothyroidism - Castillo, Oscar (2013)
A 15 year-old woman with diagnosis of hypothyroidism and hyperprolactinemia had irregular treatment. She lost conscience twice and magnetic resonance (MR) was indicated. It showed image of pituitary tumor that displaced optic chiasm. She was prescribed levothyroxin 50 ug for one week and then 100 ug daily. Hormonal treatment produced normalization of hormonal values and magnetic resonance evidenced 3 mm tumor reduction without supraselar extension.